2012
DOI: 10.1155/2012/497302
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Activity of the Ethanolic Extract fromUncaria lanosaWallich var.appendiculataRidsd in the Forced Swimming Test and in the Tail Suspension Test in Mice

Abstract: This study investigated the antidepressant activity of ethanolic extract of U. lanosa Wallich var. appendiculata Ridsd (ULEtOH) for two-weeks administrations by using FST and TST on mice. In order to understand the probable mechanism of antidepressant-like activity of ULEtOH in FST and TST, the researchers measured the levels of monoamines and monoamine oxidase activities in mice brain, and combined the antidepressant drugs (fluoxetine, imipramine, maprotiline, clorgyline, bupropion and ketanserin). Lastly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
1
17
1
2
Order By: Relevance
“…Imipramine did not significantly decrease serum TNF-α level; however, it could significantly reduce the TNF-α immune-staining in the hippocampus proper. These findings are in agreement with recent studies by Abbas et al and Hsu et al,58,59 who demonstrated that imipramine treatment increased 5-HIAA in the hippocampus of forced-swim-stressed rats and mice, respectively. Furthermore, Kubera et al60 showed that chronic treatment with imipramine reduced immune activation in rats subjected to CMS.…”
Section: Discussionsupporting
confidence: 94%
“…Imipramine did not significantly decrease serum TNF-α level; however, it could significantly reduce the TNF-α immune-staining in the hippocampus proper. These findings are in agreement with recent studies by Abbas et al and Hsu et al,58,59 who demonstrated that imipramine treatment increased 5-HIAA in the hippocampus of forced-swim-stressed rats and mice, respectively. Furthermore, Kubera et al60 showed that chronic treatment with imipramine reduced immune activation in rats subjected to CMS.…”
Section: Discussionsupporting
confidence: 94%
“…16 In addition, the FST and TST were shown to share some of the behaviours altered by depression in humans such as changes in food consumption, sleep alterations and anhedonia. 17 Duration of immobility is the indicator behaviour observed in both tests. 18 The methanol stem bark extract of A. digitata (MEAD) significantly decreased the immobility time indicating its antidepressant activity when assessed in FST and in TST.…”
Section: Resultsmentioning
confidence: 97%
“…Ethanol extract of U. lanosa stem and hook was shown to decrease the immobility time in forced swimming test and tail suspension test. And the antidepressant-like mechanism of the extract may be related with the increase in monoamines levels in the hippocampus, cortex, striatum, and hypothalamus of mice (Hsu et al, 2012). Several studies have reported that rhynchophylline (32), isorhynchophylline (40) and geissoschizine methyl ether (11) have agonistic activities on the 5-HT receptors Pengsuparp et al, 2001;Nishi et al, 2012;Ueki et al, 2013).…”
Section: Anti-depressantmentioning
confidence: 99%